External causes are leading causes of death in women of reproductive age: a registry study on maternal perinatal health, hypertensive pregnancy disorders and mortality in Finland - Saarela, Tanja; Peltomäki, Laura; Kivioja, Anna; Jääskeläinen, Tiina; Haukka, Jari; Laivuori, Hannele (BMJ PUBLISHING GROUP, 2025)
Background There is a known association between pre-eclampsia (PE) and other hypertensive disorders of pregnancy (HDP), and increased risk of cardiovascular diseases (CVD). Reproductive history is associated with maternal mortality. We studied the causes of death in women of reproductive age and how a history of HDP affects mortality.
Methods We collected and analysed the perinatal data of national registers in a study of 555 345 women born in Finland during 1966-1990. The follow-up started from the woman's first birth and ended on the first CVD, death or at the end of the follow-up of 23 years.
Results There were 295 373 women whose first birth was registered 1997-2019 and among them, 1287 deaths (cancer 493 deaths, preventable causes (suicide, accidents, alcohol, other external causes) 450 deaths, CVD 126 deaths). The diagnosis of PE or other HDP increased CVD mortality (risk ratio 2.69 (95% CI 1.40, 5.16) and 2.02 (95% CI 1.21, 3.38), respectively), compared with normotensive pregnancy. In the Poisson regression analyses, in women with other HDP than PE, a higher CVD mortality was found (mortality rate ratio 3.98, 95% CI 1.97, 8.04). Survival analysis showed reduced survival in women with PE for both CVD and all-cause mortality.
Conclusions Reproductive history, specifically preventable and CVD cause, has a significant role in mortality of women of reproductive age. Women have an increased risk of CVD death, and reduced survival of CVD mortality, if they have PE or other HDP, in the pregnancy associated with their first birth.